Produtividade do setor agrícola brasileiro (1991-2003): uma análise espacial - Almeida, Eduardo Simões de (2007)
Agricultural productivity is characterized by location patterns, represented by the so-called spatial effects, namely, spatial heterogeneity and spatial dependence. This paper analyzes the spatial effects which exert influence on agricultural land productivity at three points in time – 1991, 1997 and 2003 – at the microregional level, using exploratory spatial data analysis (ESDA). The main finding shows that agricultural productivity is increasingly self-correlated in space, over time. Two high-high (HH) clusters are identified consistently: one of them is located in the State of São Paulo and parts of the Center-West region, while the other cluster (HH) lies in the Northeastern Coast.A produtividade agrícola é marcada por padrões de localização representados pelos chamados efeitos espaciais, a saber: a heterogeneidade espacial e a dependência espacial. Assim, este trabalho analisa os efeitos espaciais que exercem influência sobre a produtividade agrícola da terra para três momentos do tempo – 1991, 1997 e 2003 – em nível microrregional. Para isso, implementa-se a análise exploratória de dados espaciais. O principal resultado mostra que a produtividade agrícola está crescentemente autocorrelacionada no espaço ao longo do tempo. Dois clusters alto-alto (AA) são identificados consistentemente: um deles localiza-se no Estado de São Paulo e partes do Centro-Oeste, enquanto o outro cluster AA situa-se no litoral nordestino